Soft magnetic material
Patent Information
- Application Number
- JP2023116405
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-01-30
AI Technical Summary
【0006】 本発明によれば、成形体としたときに強度に優れ、かつ、耐電圧性に優れた軟磁性材料を提供することができる。
Smart Images

Figure 2025014139000001
Abstract
Description
[Technical field]
[0001] The present invention relates to soft magnetic materials. [Background technology]
[0002] Soft magnetic materials are materials that are strongly magnetized in the presence of a magnetic field, but quickly lose their magnetism and return to their original state when the external magnetic field is removed. Soft magnetic materials have traditionally been used in applications such as coils for electric vehicles, home appliances, and various sensors (see, for example, Patent Document 1). In recent years, the challenge for devices using soft magnetic materials has been to achieve both high energy density and low energy loss, and there is a demand for the development of materials that can be used in high magnetic flux density and high frequency ranges. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2021-158340 A Summary of the Invention [Problem to be solved by the invention]
[0004] One possible solution to the problem of reducing energy loss is nanocrystalline soft magnetic materials, which are made by precipitating nanoscale crystals on the surface of iron through heating. However, because nanocrystalline soft magnetic materials are hard and lack flexibility, compacts made from such materials can break when compressed under high pressure to further increase density. One possible solution to the problem of increasing energy density would be to change the alloy composition that makes up the soft magnetic material (for example, by increasing the iron content), but there was concern that simply changing the alloy composition to increase energy density would result in a decrease in voltage resistance. An object of the present invention is to provide a soft magnetic material which, when formed into a compact, has excellent strength and excellent voltage resistance. [Means for solving the problem]
[0005] The present inventors conducted extensive research to solve the above problems and arrived at the present invention. That is, the present invention is as follows. [1] A soft magnetic material having soft magnetic particles and a coating portion that coats at least a portion of the particles, The volume average particle size of the soft magnetic particles is 0.1 μm to 50 μm, the coating portion contains a (meth)acrylic resin having a carboxyl group, A soft magnetic material in which the proportion of the coating portion based on the weight of the soft magnetic material is 0.55% by weight or more. [2] The soft magnetic material according to [1], wherein the proportion of the coating portion based on the weight of the soft magnetic material is 5% by weight or less. [3] The soft magnetic material according to [1] or [2], wherein the ratio of the (meth)acrylic resin having a carboxyl group based on the weight of the coating portion is 4% by weight or more and 50% by weight or less. [4] The soft magnetic material according to any one of [1] to [3], wherein the (meth)acrylic resin having a carboxyl group contains a polymer obtained by polymerizing an unsaturated carboxylic acid with two or more kinds of (meth)acrylic acid esters. Effect of the Invention
[0006] According to the present invention, it is possible to provide a soft magnetic material which, when formed into a compact, has excellent strength and voltage resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] The soft magnetic material of the present invention has soft magnetic particles and a coating that coats at least a part of the particles. In the present invention, "soft magnetic" refers to a property that is easily magnetized by an external magnetic field, but the magnetization disappears relatively easily when the magnetic field disappears. In other words, it refers to ferromagnetism with low coercive force (specifically, coercive force of 800 A / m or less).
[0008] The material of the soft magnetic particles is not particularly limited, and may be, for example, a metal-containing material containing iron as a constituent element. The metal-containing material may contain elements other than iron as a constituent element. Examples of elements other than iron include B, C, N, O, Al, Si, P, S, Ti, V, Cr, Mn, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Cd, In, and Sn. Examples of the metal-containing material include pure iron, silicon steel, iron-cobalt alloy, iron-nickel alloy, iron-chromium alloy, iron-aluminum alloy, carbonyl iron, stainless steel, and composite materials containing one or more of these. One type of metal-containing material may be used, or two or more types may be used in combination. The metal-containing material preferably contains iron and an element other than iron, and more preferably contains Fe, Si, B, P, and Cu. When the metal-containing material contains iron, the content of iron is preferably 80% (80 atm%) or more based on the number of atoms constituting the metal-containing material. As the material of the soft magnetic particles, for example, those manufactured by the gas atomization method or the water atomization method can be used. An example of a manufacturing method by the water atomization method will be described. The raw metal material is weighed in an amount that is a desired ratio, placed in a crucible, heated at a temperature of 1000 ° C. to 1500 ° C. to eject the melt, and high-pressure water is collided with the ejected melt to obtain soft magnetic powder. The obtained powder is pulverized with a pulverizer (for example, a zo crusher and a ball mill, etc.), and then classified to obtain the material of the soft magnetic particles. The soft magnetic particles may be manufactured by a method described in, for example, International Publication No. 2021 / 199970.
[0009] In the present invention, the volume average particle diameter of the soft magnetic particles is 0.1 μm to 50 μm. When the volume average particle diameter of the soft magnetic particles is 0.1 μm or more, the coating portion can be formed uniformly, and the voltage resistance can be excellent. When the volume average particle diameter of the soft magnetic particles is 50 μm or less, the packing rate of the molded body can be increased, and the material can be made suitable for high energy density applications. From the viewpoint of voltage resistance, the volume average particle diameter of the soft magnetic particles is preferably 0.5 μm or more, more preferably 1 μm or more. From the viewpoint of increasing the packing rate of the molded body, the volume average particle diameter of the soft magnetic particles is preferably 45 μm or less, more preferably 40 μm or less.
[0010] The packing ratio of the molded body is calculated by the following formula (1). Packing rate of compact (%) = [(theoretical volume of compact) / (actual volume of compact)] × 100 (1) The "actual volume of the green body" in formula (1) means the actual volume of the green body obtained by molding the soft magnetic material. The "theoretical volume of the green body" in formula (1) is the volume of the green body when there are no voids, and is calculated by the following formula (2). Theoretical volume of compact=(weight of compact) / (density of soft magnetic material) (2) The "density of the soft magnetic material" in formula (2) is a density calculated based on the composition of the materials constituting the soft magnetic material (the materials of the soft magnetic particles and coating portion).
[0011] From the viewpoint of high energy density, the packing rate of the molded body is preferably 78% or more, and more preferably 80% or more.
[0012] The volume average particle diameter of the soft magnetic particles can be measured, for example, using a laser diffraction type particle size distribution measuring device. Specifically, the soft magnetic particles are dispersed in a dispersion medium such as water to prepare a dispersion liquid. When a volume cumulative distribution curve is drawn from the small diameter side using a laser diffraction type particle size distribution measuring device for this dispersion liquid, the particle diameter (D50) at cumulative 50% is defined as the volume average particle diameter.
[0013] From the viewpoint of reducing energy loss, it is preferable that the soft magnetic particles (soft magnetic particles before the formation of the coating portion) have nano-sized crystals precipitated on the surface. The particles having nano-sized crystals precipitated thereon can be produced, for example, by heat treatment at 500°C to 800°C for 30 minutes to 2 hours.
[0014] In the present invention, the coating portion is a portion that coats at least a portion of the soft magnetic particle, and preferably coats the entire surface of the soft magnetic particle.
[0015] In the present invention, the ratio of the coating portion based on the weight of the soft magnetic material is 0.55% by weight or more. By having the ratio of the coating portion be 0.55% by weight or more, it is possible to provide a soft magnetic material that has excellent strength and excellent voltage resistance when formed into a molded body. From the viewpoint of strength and voltage resistance when formed into a molded body, the ratio of the coating portion based on the weight of the soft magnetic material is preferably 1.5% by weight or more, more preferably 2% by weight or more. In addition, from the viewpoint of heat resistance, the ratio of the coating portion based on the weight of the soft magnetic material is preferably 5% by weight or less, more preferably 2.5% by weight or less.
[0016] In the present invention, the coating portion contains a (meth)acrylic resin (A) having a carboxyl group. In this specification, "(meth)acrylic resin" means "acrylic resin and / or methacrylic resin". By containing a (meth)acrylic resin having a carboxyl group, the strength of the soft magnetic material when molded into a molded body can be excellent. Although the details of the mechanism of such an effect are unclear, it is presumed as follows. By containing a (meth)acrylic resin having a carboxyl group in the coating portion, the carboxyl group in the coating portion is strongly bonded to the soft magnetic particles, and the adhesion between the coating portion and the soft magnetic particles is increased, so that the soft magnetic particles can be compressed in a coated state even when molded under high pressure. Then, the carboxyl groups contained in the coating portion interact with each other when compressed, improving the strength of the molded body.
[0017] Examples of the (meth)acrylic resin (A) having a carboxyl group include a polymer containing a structural unit derived from an unsaturated carboxylic acid (a1) and a structural unit derived from a (meth)acrylic acid ester (a2). In this specification, (meth)acrylic acid means acrylic acid and / or methacrylic acid.
[0018] The unsaturated carboxylic acid (a1) may be an unsaturated carboxylic acid having 3 to 10 carbon atoms, such as acrylic acid, methacrylic acid, maleic acid, or 3-allyloxypropionic acid. Of these, acrylic acid and methacrylic acid are preferred from the viewpoint of adhesion to soft magnetic particles. The unsaturated carboxylic acid (a1) may be used alone or in combination of two or more.
[0019] Examples of the (meth)acrylic acid ester (a2) include (meth)acrylic acid alkyl ester (a21) having an alkyl group having 1 to 18 carbon atoms and (meth)acrylic acid ester (a22) of an alkanediol having 2 to 18 carbon atoms. The (meth)acrylic acid ester (a2) may be used alone or in combination of two or more kinds.
[0020] In the (meth)acrylic acid alkyl ester (a21) having an alkyl group having 1 to 18 carbon atoms, examples of the alkyl group having 1 to 18 carbon atoms include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, a neopentyl group, an isopentyl group, a hexyl group, a heptyl group, an octyl group, a 2-ethylhexyl group, an isooctyl group, a nonyl group, an isononyl group, a decyl group, an isodecyl group, an undecyl group, a dodecyl group, a tridecyl group, a tetradecyl group, a pentadecyl group, a hexadecyl group, a heptadecyl group, a stearyl group, and an isostearyl group.
[0021] Examples of the (meth)acrylic acid alkyl ester (a21) include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, neopentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, Examples of such acrylates include 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, stearyl (meth)acrylate, and isostearyl (meth)acrylate. Of these, from the viewpoint of adhesion to soft magnetic particles, methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and combinations thereof are preferred, with 2-ethylhexyl (meth)acrylate being more preferred.
[0022] Examples of the alkanediol having 2 to 18 carbon atoms in the ester (a22) of an alkanediol having 2 to 18 carbon atoms and (meth)acrylic acid include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, octanediol, decanediol, dodecanediol, hexadecanediol, neopentyl glycol, and 2,2-diethyl-1,3-propanediol.
[0023] The ester (a22) of an alkanediol having 2 to 18 carbon atoms and (meth)acrylic acid may be a monoester or a diester. From the viewpoint of adhesion to soft magnetic particles, the ester (a22) of an alkanediol having 2 to 18 carbon atoms and (meth)acrylic acid is preferably a di(meth)acrylate of an alkanediol having 4 to 10 carbon atoms, more preferably a di(meth)acrylate of 1,6-hexanediol. In this specification, (meth)acrylate means acrylate and / or methacrylate.
[0024] The polymer containing a structural unit derived from an unsaturated carboxylic acid (a1) and a structural unit derived from a (meth)acrylic acid ester (a2) is obtained by polymerizing a monomer component containing an unsaturated carboxylic acid (a1) and a (meth)acrylic acid ester (a2). The polymer is preferably a polymer obtained by polymerizing an unsaturated carboxylic acid and two or more kinds of (meth)acrylic acid esters, more preferably a polymer obtained by polymerizing an unsaturated carboxylic acid, two or more kinds of (meth)acrylic acid alkyl esters, and an ester of an alkanediol and (meth)acrylic acid, and even more preferably a polymer obtained by polymerizing (meth)acrylic acid, two or more kinds of (meth)acrylic acid alkyl esters, and cyclohexanediol.
[0025] When the (meth)acrylic resin (A) having a carboxyl group contains a polymer containing a constitutional unit derived from an unsaturated carboxylic acid (a1) and a constitutional unit derived from a (meth)acrylic acid ester (a2), the weight ratio of the unsaturated carboxylic acid (a1) in the monomer components constituting the polymer is preferably 3 to 10% by weight, more preferably 4 to 8% by weight, based on the weight of the polymer. The weight ratio of the (meth)acrylic acid ester (a2) in the monomer components constituting the polymer is preferably 90 to 93% by weight, more preferably 92 to 96% by weight, based on the weight of the polymer.
[0026] When the (meth)acrylic resin (A) having a carboxyl group contains a polymer containing a constitutional unit derived from an unsaturated carboxylic acid (a1) and a constitutional unit derived from a (meth)acrylic acid ester (a2), the weight ratio of the unsaturated carboxylic acid (a1) in the monomer components constituting the polymer is preferably 3 to 10% by weight, more preferably 4 to 8% by weight, based on the weight of the polymer. The weight ratio of the (meth)acrylic acid ester (a2) in the monomer components constituting the polymer is preferably 90 to 93% by weight, more preferably 92 to 96% by weight, based on the weight of the polymer.
[0027] An example of a method for producing the (meth)acrylic resin (A) having a carboxyl group in the present invention will be described. When the resin (A) is a resin containing a polymer containing a structural unit derived from an unsaturated carboxylic acid (a1) and a structural unit derived from a (meth)acrylic acid ester (a2), the resin can be produced by polymerizing a monomer component containing the unsaturated carboxylic acid (a1) and the (meth)acrylic acid ester (a2) by a known method.
[0028] The weight average molecular weight (Mw) of the (meth)acrylic resin (A) having a carboxyl group is preferably 100,000 to 150,000 from the viewpoint of voltage resistance and the like. The Mw of a resin can be measured by gel permeation chromatography (GPC) under the following conditions, for example. Equipment: "HLC-8120GPC" [Tosoh Corporation] Columns: "Guardcolumn HXL-H" (1 unit), "TSKgel GMHXL" (2 units) [both manufactured by Tosoh Corporation] Sample solution: 0.25% by weight tetrahydrofuran solution Solution injection volume: 100μl Flow rate: 1ml / min Measurement temperature: 40℃ Detector: Refractive index detector Reference material: Standard polystyrene
[0029] From the viewpoint of excellent adhesion to the soft magnetic particles and excellent strength when molded, the content of the (meth)acrylic resin (A) having a carboxyl group in the coating is preferably 1% by weight or more, more preferably 4% by weight or more, and even more preferably 4.8% by weight or more, based on the weight of the coating. From the viewpoint of excellent voltage resistance, the content of the (meth)acrylic resin (A) having a carboxyl group in the coating is preferably 55% by weight or less, more preferably 50% by weight or less, based on the weight of the coating.
[0030] The coating portion may contain a resin that does not have a carboxyl group. An example of the resin that does not have a carboxyl group is a (meth)acrylic resin (A') that does not have a carboxyl group. Hereinafter, the (meth)acrylic resin (A') that does not have a carboxyl group may be referred to as "(meth)acrylic resin (A')". An example of the (meth)acrylic resin (A') is one that has a structural unit derived from a (meth)acrylic acid ester. An example of the (meth)acrylic acid ester that is a structural unit of the (meth)acrylic resin (A') is the same as the (meth)acrylic acid ester (a2) that is a structural unit of the (meth)acrylic resin (A) that has a carboxyl group. From the viewpoint of adhesion to soft magnetic particles, the (meth)acrylic resin (A') preferably contains a polymer obtained by polymerizing two or more (meth)acrylic acid esters, more preferably contains a polymer obtained by polymerizing two or more (meth)acrylic acid alkyl esters and an ester of an alkanediol and (meth)acrylic acid, and even more preferably contains a polymer obtained by polymerizing two or more (meth)acrylic acid alkyl esters and cyclohexanediol.
[0031] When the coating contains a resin having no carboxyl groups, from the viewpoints of excellent adhesion to the soft magnetic particles and excellent strength when formed into a molded product, the content of the resin having no carboxyl groups in the coating is preferably 45% by weight or more, more preferably 50% by weight or more, based on the weight of the coating, and from the viewpoint of excellent voltage resistance, the content of the resin having no carboxyl groups in the coating is preferably 99% by weight or less, more preferably 95.2% by weight or less, based on the weight of the coating.
[0032] The manufacturing method of the soft magnetic material of the present invention will be described. The soft magnetic material can be manufactured, for example, by a manufacturing method including a step 1 of mixing soft magnetic particles, a coating material, and a solvent to obtain a mixture, and a step 2 of volatilizing the solvent in the mixture to obtain soft magnetic particles having a coating.
[0033] Step 1 is a step of mixing soft magnetic particles, a coating material (a material containing a (meth)acrylic resin (A) having a carboxyl group) and a solvent to obtain a mixture. The soft magnetic particles used in step 1 can be the same as the soft magnetic particles described above. The coating material (a material forming the coating) is a material containing a (meth)acrylic resin (A) having a carboxyl group. As the material, a resin without a carboxyl group can be used together with the resin (A).
[0034] The solvent used in step 1 may be an organic solvent (e.g., a lower alcohol such as isopropyl alcohol, toluene, etc.). The type and amount of the solvent may be set in consideration of the types of the soft magnetic particles and the material of the coating portion (material for forming the coating portion). The mixing conditions (mixing time, mixing device, mixing temperature, etc.) when mixing the soft magnetic particles, the material of the coating portion, and the solvent may be set in consideration of the types and amounts of the materials used.
[0035] Step 2 is a step of obtaining soft magnetic particles having a coating portion by volatilizing the solvent in the mixture obtained in step 1. The method of volatilizing the solvent (temperature, time, etc.) can be set in consideration of the type and amount of the solvent used.
[0036] The particles obtained after the completion of step 2 may be used as the soft magnetic material as it is, or the particles obtained in step 2 may be classified to have a predetermined particle size. The classification method is not particularly limited, but may be performed, for example, by using a sieve with an opening size of 200 to 300 μm. The volume average particle size of the soft magnetic material is preferably 0.1 μm to 50 μm from the viewpoint of the packing rate.
[0037] The soft magnetic material of the present invention can be molded into a molded article using a mold or the like having a shape according to the intended use. The molding conditions can be set according to the intended use, and can be, for example, a molding pressure of 100 MPa to 500 MPa and a molding time of 10 seconds to 60 seconds.
[0038] There is no particular limitation on the applications of the soft magnetic material of the present invention, but since the material has excellent strength when molded into a compact and excellent voltage resistance, it is suitable as a material for magnetic cores for coil components. EXAMPLES
[0039] The present invention will be further described below with reference to examples and comparative examples, but the present invention is not limited thereto. In the following, % means % by weight, and parts means parts by weight, unless otherwise specified.
[0040] <Production Example 1: Production of (meth)acrylic resin (A-1) having a carboxyl group> 4.6 parts of methacrylic acid, 65 parts of 2-ethylhexyl methacrylate, 30 parts of 2-ethylhexyl acrylate, 0.4 parts of 1,6-hexanediol diacrylate and 60 parts of isopropanol were added and stirred at a stirring speed of 30 rpm for 30 minutes to prepare a monomer liquid. 0.26 parts of a reaction initiator (azo polymerization initiator V-65, manufactured by Fuji Film Corporation) was dissolved in 12 parts of isopropanol to prepare an initiator solution. The monomer liquid and the initiator liquid were added dropwise to the reaction vessel (monomer liquid drop rate: 73.33 g / min, initiator liquid drop rate: 9.03 g / min), stirred at a stirring speed of 35 rpm, and reacted at a reaction temperature of 70° C. for 120 minutes. Next, the initiator liquid was added to the reaction vessel (dropping rate of the initiator liquid: 9.03 g / min), the mixture was stirred at a stirring speed of 35 rpm, the reaction temperature was set to 80° C., and the reaction was carried out for 120 minutes to obtain a product. The product obtained after the reaction was designated as (meth)acrylic resin (A-1).
[0041] <Production Example 2: Production of (meth)acrylic resin (A-2) having no carboxyl group> The same procedure as in Production Example 1 was carried out except that 4.6 parts of methacrylic acid was not used, to obtain a (meth)acrylic resin (A-2).
[0042] <Preparation of soft magnetic particles used in examples and comparative examples> (1) Preparation of soft magnetic powder The metal raw materials were weighed out so that the atomic ratio of Fe:Si:B:P:Cu was 83.5:4.5:7.5:4:0.5, and placed in a crucible and heated at 1600°C. The molten liquid in the crucible was ejected and high-pressure water was collided with the ejected molten liquid to produce soft magnetic powder (Fe 83.5 S 4.5 B 7.5 P 4 Cu 0.5 The obtained soft magnetic powder was pulverized in a ball mill, and then classified using a sieve with 20 μm openings to prepare powder B1, and powder B2, which passed through a sieve with 125 μm openings but not a sieve with 75 μm openings. The following materials were used as metal raw materials. Fe: Myron (purity 99.95%) manufactured by Toho Zinc Co., Ltd. Si: Granular silicon (purity 99.999%) manufactured by High Purity Chemical Laboratory Co., Ltd. B: Granular boron (purity 99.5%) manufactured by High Purity Chemical Laboratory Co., Ltd. P: Lump iron phosphide Fe3P (purity 99%) manufactured by Kojundo Chemical Laboratory Co., Ltd. Cu: Copper chips (purity 99.9%) manufactured by Kojundo Chemical Laboratory Co., Ltd.
[0043] (2) Manufacturing of soft magnetic particles The powder obtained in (1) (Fe 83.5 S 4.5 B 7.5 P 4 Cu 0.5 ) B1 and B2 were each heat-treated in an Ar atmosphere at 700° C. for 1 hour to obtain soft magnetic particles. The particle surfaces were observed with a transmission electron microscope (JEM-1400Flash, manufactured by JEOL Ltd.), and it was confirmed that nano-sized crystals were precipitated on the particle surfaces. In addition, the volume average particle diameter of the particles after heat treatment was measured using a laser diffraction particle size distribution measuring device [manufactured by Microtrackbell Co., Ltd., product name "SLAMT3000II"].The volume average particle diameter of the particles obtained by heat treating B1 was 10 μm [referred to as soft magnetic particles (B-1)], and the volume average particle diameter of the particles obtained by heat treating B2 was 100 μm [referred to as soft magnetic particles (B-2)].
[0044] <Measurement of physical properties of the material (resin) of the covering part used in the examples and comparative examples> The physical properties of the resin material used to form the coating portion (A) in each example were measured by the following method. The results are shown in Table 1. The resin material in each example was a mixture of the types of resins shown in Table 1 in the ratios shown in Table 1. For example, in the case of Example 1, a mixture of a (meth)acrylic resin (A-1) having a carboxyl group and a (meth)acrylic resin (A-2) not having a carboxyl group in an amount of (A-1):(A-2) of 0.09:1.73 was evaluated. For Comparative Example 3, only a silicone resin [Shin-Etsu Silicone KR-251, manufactured by Shin-Etsu Chemical Co., Ltd.] was used.
[0045] (Peel strength measurement) The peel strength of the resin material used to form the coating part (A) used in each example was measured in accordance with the method specified in JIS K6854-3 (Adhesives - Peel Adhesion Strength Test Method Part 3) using 20 μm thick copper foil as the flexible adherend, with the adherend size of 5 cm in length, 1.5 cm in width, and 1 cm x 1 cm in adhesive area, at a peel speed of 10 mm / min. The higher the peel strength, the higher the adhesion to the metal material. The peel strength was 3 N / cm 2 More preferably, it is equal to or greater than this.
[0046] (Weight loss temperature measurement) The peel strength of the resin material for forming the covering portion (A) used in each example was measured by the weight loss temperature in the method specified in JIS K7120 (thermogravimetric measurement method for plastics) with a measurement range of 20°C to 500°C and a heating rate of 20°C / min. The weight loss temperature is the temperature at which the weight is reduced by 5% from the initial weight, and the higher the temperature, the better the heat resistance. The weight loss temperature is preferably 250°C or higher.
[0047] <Example 1> (1) Manufacturing of soft magnetic materials To 7 parts of the soft magnetic particles (B-1), the materials for the coating portion [0.007 parts of a (meth)acrylic resin (A-1) having a carboxyl group and 0.136 parts of a (meth)acrylic resin (A-2) not having a carboxyl group] and 0.7 parts of isopropanol (solvent) were added, and the mixture was stirred at 2000 rpm for 90 seconds using a stirrer [Awatori Rentaro ARE-310, manufactured by Thinky Corporation] to obtain a mixture. The obtained mixture was heated at 120° C. for 1 hour to remove isopropanol, thereby obtaining soft magnetic particles having a coating portion. The soft magnetic particles having the coating portion were passed through a sieve with an opening of 250 μm, and the particles that passed through the sieve were used as the soft magnetic material of Example 1.
[0048] (2) Manufacturing of compacts using soft magnetic materials The soft magnetic material produced in (1) was filled into a circular tablet mold with a radius of 15 mm to a predetermined thickness (0.5 mm or 2 mm). The circular tablet mold was set in a tablet molding machine ["HANDTAB-100", manufactured by Ichihashi Seiki Co., Ltd.] and pressurized at 392 MPa (4000 kgf / cm 2The soft magnetic material was then removed from the molding machine and heated at 150°C for 1 hour to obtain a disk-shaped compact. Compacts with a thickness of 0.5 mm and 2 mm were produced. Evaluation tests were carried out on the obtained compacts. The results are shown in Table 1.
[0049] <Examples 2 to 6 and Comparative Examples 1 to 4> The soft magnetic materials of Examples 2 to 6 and Comparative Examples 1 to 4 were manufactured by the same procedure as in Example 1, except that the types of materials shown in Table 1 were used in the proportions shown in Table 1. In addition, the green bodies of Examples 2 to 6 and Comparative Examples 1 to 4 were manufactured by the same procedure as in Example 1, and evaluation tests were performed. The results are shown in Table 1.
[0050] The materials listed in Table 1 are as follows: <Material of the covering part (A)> (A-1): (meth)acrylic resin having a carboxyl group produced in Production Example 1 (A-2): (meth)acrylic resin having no carboxyl group produced in Production Example 2 (A-3): Silicone resin [Shin-Etsu Silicone KR-251, manufactured by Shin-Etsu Chemical Co., Ltd.] <Soft magnetic particles (B)> (B-1): Soft magnetic particles with a volume average particle size of 10 μm (Fe 83.5 S 4.5 B 7.5 P 4 Cu 0.5 ) (B-2): Soft magnetic particles with a volume average particle size of 100 μm (Fe 83.5 S 4.5 B 7.5 P 4 Cu 0.5 ) <Solvent (C)> (C-1): Isopropanol
[0051] <Evaluation test of molded body> (Calculation of filling rate) (i) The thickness and weight of the molded product are measured. Using the measured thickness value of the molded product, the actual volume of the molded product is calculated according to the following formula. Actual volume of compact=(thickness of compact)×(area of circular tablet mold) (ii) Calculate the "density of the soft magnetic material" based on the composition of the materials constituting the soft magnetic material (materials of the soft magnetic particles and coating portion). Calculate the theoretical volume of the compact using the calculated density of the soft magnetic material and the measured weight of the compact measured in (i). Theoretical volume of compact=(weight of compact) / (density of soft magnetic material) (iii) Calculate the packing ratio of the molded body using the following formula. Filling rate (%) = [(theoretical volume of green body) / (actual volume of green body)] × 100 The filling rate of the molded body is preferably 78% or more.
[0052] (Strength measurement: using a 2mm thick molded body) (i) A molded body having a thickness of approximately 2 mm is placed between the plates of a compression device [Autograph AG-100KNG, manufactured by Shimadzu Corporation] and positioned so that its central axis direction (thickness direction) is parallel to the horizontal plane of the plates. (ii) The upper plate is lowered at a speed of 1 mm / min to compress the compact, and the maximum pressure (N / mm 2 ) (referred to as "breaking pressure" in Table 1) was measured. The higher the maximum pressure, the higher the strength. The maximum pressure was 45N / mm 2 The above is preferred.
[0053] (Measurement of resistivity) (i) Fine particle carbon grease is applied to the top and bottom surfaces (circular surfaces) of a molded body with a thickness of approximately 0.5 mm to improve conductivity. The resistance of the molded body is measured by placing terminals of a tester [Insulation Resistance Meter MG1000, Sanwa Electric Instruments Co., Ltd.] on the top and bottom surfaces of the molded body. The measured value, the thickness of the sample (molded body), and the area of the molded body are applied to the following formula to calculate the resistivity of the molded body. The area of the molded body is the average area of the top and bottom surfaces of the molded body. Resistivity of molded body=(measured resistance value)×(area of molded body) / (thickness of molded body) The higher the resistivity, the better the voltage resistance, and a resistivity of 100 Ω·m or more is preferable.
[0054] [Table 1]
[0055] As shown in Table 1, the compacts of the examples had a higher breakdown pressure than the compacts of the comparative examples. In addition, all of the compacts of the examples had high resistivity. From these results, it was found that the present invention can provide a soft magnetic material that has excellent strength and voltage resistance when made into a compact.
Claims
1. A soft magnetic material having soft magnetic particles and a coating portion that coats at least a portion of the particles, The volume average particle size of the soft magnetic particles is 0.1 μm to 50 μm, the coating portion contains a (meth)acrylic resin having a carboxyl group, A soft magnetic material in which the proportion of the coating portion based on the weight of the soft magnetic material is 0.55% by weight or more.
2. 2. The soft magnetic material according to claim 1, wherein the ratio of the coating portion to the weight of the soft magnetic material is 5% by weight or less.
3. 3. The soft magnetic material according to claim 1, wherein the ratio of the (meth)acrylic resin having a carboxyl group to the weight of the coating portion is 4% by weight or more and 50% by weight or less.
4. 3. The soft magnetic material according to claim 1, wherein the (meth)acrylic resin having a carboxyl group comprises a polymer obtained by polymerizing an unsaturated carboxylic acid with two or more kinds of (meth)acrylic acid esters.
Citation Information
Patent Citations
Magnetic core, magnetic component, and electronic device
JP2021158340A